A STUDY ON THE DEVELOPMENT OF SKIMMING SKILLS IN INTERMEDIATE STUDENTS VIA CONTENT-BASED LEARNING - Keruenbaeva Amina Muxammad qizi; Khayrullayeva Dilorom (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This research project aims to improve skimming skills among intermediate (B1) level students using a Content-Based Learning (CBL) approach. The topic of climate change was chosen to integrate meaningful content into reading instruction, enhancing student motivation and comprehension. The study investigates how CBL, by embedding skimming strategies in content-rich texts, can improve students’ reading speed, ability to identify main ideas, and overall reading fluency.